Evaluative Experiments of a Fellow Passenger Robot Using a Driving Simulator. (4th February 2013) - Tanaka, Yumi; Hashimoto, Minoru
We studied how a fellow passenger robot influences drivers. The fellow passenger robot was designed to move and speak as if it knows the surroundings of the car. We conducted experiments with a driving simulator and evaluated the effectiveness of the robot with various methods. We used questionnaires to ask for impressions of the driving experience for the participants after the driving experiments with the fellow passenger robot. In addition, the car speed, acceleration and steering angle were measured during the driving experiments. Some significant differences between experiences with and without robot were found in the results with regard to impression evaluation and average speed. Therefore, we found that the robot makes driving more enjoyable and that drivers drive slower than without the robot.